1980
DOI: 10.7326/0003-4819-92-6-837
|View full text |Cite
|
Sign up to set email alerts
|

Words as Scalpels: Transmitting Evidence in the Clinical Dialogue

Abstract: This paper examines rationales and policies developed by physicians through history about what to tell patients found to have serious illness. The widespread belief among doctors that the revelation of threatening news causes patients considerable anguish and seriously erodes the prospect of maintaining their hope encouraged a policy of concealment for many centuries. Arguments that encourage candor have been increasingly pressed during the last two centuries. Advocates point out that candor can be beneficial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 8 publications
0
24
0
Order By: Relevance
“…Ironically, although the majority of families advocated telling patients, most felt that it had not been helpful for their own family member to have been told and fewer than half felt that their affected family member was able to understand the diagnosis when told. This might re¯ect the current societal values exalting the importance of full disclosure, which has increased in recent years (Blumen®eld et al, 1978;Reiser, 1980), despite the observed outcomes reported by family members.…”
Section: Discussionmentioning
confidence: 85%
“…Ironically, although the majority of families advocated telling patients, most felt that it had not been helpful for their own family member to have been told and fewer than half felt that their affected family member was able to understand the diagnosis when told. This might re¯ect the current societal values exalting the importance of full disclosure, which has increased in recent years (Blumen®eld et al, 1978;Reiser, 1980), despite the observed outcomes reported by family members.…”
Section: Discussionmentioning
confidence: 85%
“…A 1979 replication of the Oken (1961) study revealed that 98% of 264 physicians affirmed the value of providing detailed information to cancer patients, and 100% endorsed the patient's right to be informed of the diagnosis (Novack et al, 1979). Various reasons have been offered to account for this shift in clinician behaviour, including: (1) an increased fear of litigation among physicians, (2) the publication of guidelines for the disclosure of diagnoses (Reiser, 1980), (3) more effective therapies for cancer patients through technological advancement and (4) a change in public opinion regarding patients' rights to medical information and full disclosure (Thomasma, 1983).…”
mentioning
confidence: 99%
“…. have through this cause taken a turn for the worst (1). Oliver Holmes wrote in 1883 that "[y]our patients have no more right to all the truth you know than he has to all the medicine in your saddlebag.…”
Section: Introductionmentioning
confidence: 97%
“…Oliver Holmes wrote in 1883 that "[y]our patients have no more right to all the truth you know than he has to all the medicine in your saddlebag. He should get only as much as is good for him" (1). Another nineteenth-century physician Worthington Hooker argued against the commonly held assumption that truth-telling harmed the patient and felt from a moral standpoint that lying was unacceptable (1).…”
Section: Introductionmentioning
confidence: 99%